Acceptance and effectiveness for learning of a simulation manikin for suprapubic aspiration in toddlers constructed with simple means. (December 2015) - Bosse, Hans; Martin, Alice; Ling, Kerstin; Memili, Suzan; Patalong, Silvan; Rings, Veronika; Jasper, Elisabeth; Luczak, Katharina; Liesenjohann, Svenja; Witsch, Alix; Wengel, Carolin
Abstract Background Skills trainings are increasing in popularity in undergraduate medical education enhancing clinical competencies and motivation for clinical practice. A suprapubic aspiration (SPA) is the gold standard to obtain urine from toddlers and young infants with fever and unclear focus to prove an urinary tract infection. Methods In a blended-learning scenario with virtual patients and skills lab training students were trained for a SPA. Currently, no toddler simulation manikin for SPA is available on the market so we constructed one with simple means. Students' acceptance and their view on relevant aspects of the manikin for learning effectiveness were assessed. Results With an expenditure regarding work of 3½ h and material costs of 188.12 Euro we were able to construct a paediatric manikin for suprapubic bladder punction using a cheap basic life support manikin. N = 56 students rated their learning success with the manikin as high (77.2 ± 21.6; mean and standard deviation; visual analogue scales from 100 = totally agree to 0 = don't agree at all). The model was rated as useful for training (84.2 ± 17.2) and realistic (62.1 ± 23.5). Important factors for students' learning success were (in descending order) that "urine" could be aspirated (81.4 ± 19.5), the feel of the needle inserted in the manikin (71.5 ± 23.2), and—notably less important—the outer appearance in general (40.3 ± 24.6). Conclusions We present a construction of a paediatric manikin for suprapubic aspiration with simple means for a realistic learning scenario with high learning success.